How is the Compliance of Micro, Small and Medium Taxpayers (Case Study on MSME in the City of Mataram) - Sofhia, Sofhia; Husnaini, Wahidatul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze in depth how taxpayer compliance in fulfilling tax obligations in the era of digitalization. This study uses qualitative with a case study approach. Researchers conduct data collection techniques through interviews (semi-structured), observation, and documentation. 9 MSME informants and two large business informants were selected using purposive sampling. The study results show that 3 out of 9 MSMEs remain compliant despite experiencing difficulties operating digital electronic systems by utilizing available services. Meanwhile, one MSME was identified as non-compliant because they needed to understand the concept of taxation and the digital tax system. One other MSME was identified as non-compliant even though they understood the electronic tax system. The Digital Empowerment Theory is supported, which shows the need for comprehensive socialization in various business fields.